Salivary analysis and oral symptoms in controlled asthmatic patients (Mustansiria Dental Journal, 2005)
Asthma is a common inflammatory condition of lung airways. Its cause isincompletely understood .Patients with bronchial asthma are affected both by the disease and its treatment .The purpose of our study was to examine the salivary composition in asthmatic patients ,and study the association between asthma and occurrence of selected oral symptoms .The study was divided into two phases. In the first phase (salivary analysis) thesalivary composition and unstimulated salivary flow rates of 50 asthmatic patients werecompared with that of 25 non -asthmatic subjects. In the second phase (questionnairsurvey) the occurrence of symptoms of oral diseases in asthmatics (n=I I3) was comparedwith that of non—asthmatic subjects (n=ll I .)In addition to the symptoms of oral diseases, data on background informationwere taken. The results of salivary analysis showed no statistically significant differencesbetween the asthmatic and non- asthmatics concerning the salivary flow rate andcomposition, However, the asthmatic saliva samples showed lower potassium and higherinorganic phosphorus levels .In the questionnair survey , the subjects reported more symptoms (dry mouth ,soremouth , halitosis , pain in Temporomandibular jiont (TMI) , stuffiness in (TMI) andclicking in (TMI) compaired to the controlled group. The presence of asthmaprecipitating factors and medication used had a considerable effect on the probability ofhaving symptoms of oral diseases when compaired to non- users